A atualidade do conceito indústria cultural : reflexão sobre a educação danificada - Loibel, Tadeu Cândido Coelho (2012)
In this dissertation is presented a discussion about semi-formação (semiformation) from the idea formulated by Theodor Adorno "education by hardness . For this is discussed the actuality of Cultural industry concept, also of Adorno, since the semi-formação (semi-formation) is the expression of this in education, with the contribution of Max Horkheimer, based on the analysis of some criticisms from commentators who are against the vality of the Cultural Industry.